2024
DOI: 10.3390/jcm13040961
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of New Cardiac Damage Biomarkers in Polytrauma: GDF-15, HFABP and uPAR for Predicting Patient Outcomes

Aileen Ritter,
Lorenz Lötterle,
Jiaoyan Han
et al.

Abstract: Background: Polytrauma is one of the leading mortality factors in younger patients, and in particular, the presence of cardiac damage correlates with a poor prognosis. Currently, troponin T is the gold standard, although troponin is limited as a biomarker. Therefore, there is a need for new biomarkers of cardiac damage early after trauma. Methods: Polytraumatized patients (ISS ≥ 16) were divided into two groups: those with cardiac damage (troponin T > 50 pg/mL, n = 37) and those without cardiac damage (trop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…In the present study, we propose the suitability of SEC-isolated EVs for polytrauma research and showed that such EVs could be used in a differential analysis of EV surface epitopes [ 20 , 21 ] and/or a cargo analysis of cytokines [ 22 ] and miRNAs [ 23 ]. It is known that isolation methods can influence the measured total protein content of EVs [ 24 ], as well as the EV-particle number [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we propose the suitability of SEC-isolated EVs for polytrauma research and showed that such EVs could be used in a differential analysis of EV surface epitopes [ 20 , 21 ] and/or a cargo analysis of cytokines [ 22 ] and miRNAs [ 23 ]. It is known that isolation methods can influence the measured total protein content of EVs [ 24 ], as well as the EV-particle number [ 25 ].…”
Section: Discussionmentioning
confidence: 99%